The impact of company-specific factors on accounting-based performance: evidence from the Malaysian listed companies - Ismail, Rusmawati; Abdullah, Nur Adiana Hiau; Taufil Mohd, Kamarun Nisham (2016)
The main objective of this paper is to examine the influence of both lagged and contemporaneous risk-taking as well as other company-specific factors on performance of non-financial Malaysian listed companies.This study will cover an observation period of 12 years (2004 to 2015) on unbalanced panel data basis.In order to deal with the dynamic nature of downside risk-return relationship, the dynamic panel estimation will be carried out using two-step system generalized method of moments (S-GMM) estimator.The application of S-GMM which is claimed as robust in the class of all GMM estimators, could offer a better explanation on the issue discussed.For the management of a company, this research outcome may strategically provide guidance on planning and managing their investment activities to increase shareholders’ wealth. A better assessment of risk would eventually contribute to wealth creation. In terms of investors, the results could enhance their awareness and understanding of the collective investment behaviour of companies. Hence, it could assist them to select the appropriate investment according to their risk preferences. With regard to the Securities Commission (SC), the outcomes could furnish this regulatory body with more accurate risk-return assessment model. In line with SC’s statutory function, this security market supervisory body is obligated to encourage the application of reliable risk measure amongst stakeholders.By facilitating market participants with informative investment guidance, greater development of securities market in Malaysia would be promoted.